Pengaruh kecerdasan emosi dan efikasi terhadap stail pengurusan disiplin guru di Kedah dan Perlis - Nazri, Halim (2018)
The teacher’s management disciplinary style are procedures used by the teachers to discipline the students in school. However, there were some teachers did not comply with the discipline procedures designed by the Ministry of Education (MoE). Report from the State Education Department of Kedah and Perlis showed that some teachers reacted aggressively while handling student’s disciplinary cases. This clearly showed the lack of influence of emotional intelligence and teacher’s efficacies owned by them. Thus, the objective of the study was to study the influence of emotional intelligence and efficacy on teachers’ management disciplinary styles. The appropriate teacher’s management disciplinary style was being identified through the strongest influence of emotional intelligence and teacher’s efficacy. The teacher’s management disciplinary styles of this study are the supporter, negotiator, compromiser, abdicator, and enforcer. The cross-sectional design which was used in this survey study involved 320 teachers from the primary school’s disciplinary committee. Instruments used in this study were Emotional Competency Inventory version 2 (ECI-v2), Teacher’s Sense of Efficacy Scale (TSES) and The Teacher Discipline Five Style Inventory Model. The findings showed that emotional intelligence and teacher’s efficacy have given the strongest influences on the negotiator’s management disciplinary style compared to the supporter’s and compromiser’s management disciplinary styles. However, emotional intelligence did not have any influence on the enforcer’s management disciplinary style, while teacher’s efficacy did not have any influence on the abdicator’s management disciplinary style. This study also showed that emotional intelligence is a significant partial mediator to the compromiser, abdicator, supporter and negotiator management disciplinary styles. The findings of this study can contribute to Ministry of Education (MoE) as a guide for the selection of disciplinary teachers and to identifies school teachers’ management disciplinary style to make necessary disciplinary reinforcement and prevention.